Review of the systematics, biology and ecology of lice from pinnipeds and river otters (Insecta: Phthiraptera: Anoplura: Echinophthiriidae) - Leonardi, Maria Soledad; Palma, Ricardo Luis (Zootaxa, 2013)
We present a literature review of the sucking louse family Echinophthiriidae, its five genera and twelve species parasitic on pinnipeds (fur seals, sea lions, walruses, true seals) and the North American river otter. We give detailed synonymies and published records for all taxonomic hierarchies, as well as hosts, type localities and repositories of type material; we highlight significant references and include comments on the current taxonomic status of the species. We provide a summary of present knowledge of the biology and ecology for eight species. Also, we give a host-louse list, and a bibliography to the family as complete as possible.